2021
DOI: 10.1101/2021.10.17.464729
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative genomics of Xylella fastidiosa suggests determinants of host-specificity and expands its mobile genetic elements repertoire

Abstract: The Gram-negative bacterium Xylella fastidiosa colonizes plant xylem vessels and is obligately vectored by xylem sap-feeding hemipteran insects. X. fastidiosa causes diseases in many plant species but in a variety of its plant hosts this bacterium behaves as a commensal endophyte. Originally confined to the Americas, infecting mainly grapevine, citrus and coffee plants, X. fastidiosa has spread to several plant species in Europe, causing devastating crop diseases. Although many pathogenicity and virulence fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 110 publications
0
2
0
Order By: Relevance
“…After building a phylogeny, they tested coevolutionary relationships between host species and X. fastidiosa MLST types but found no significant evidence of coevolution, implying a lack of host specialization. This topic was recently revisited with full genome data (26,27), but the results were inconsistent between studies. Uceda-Campos et al ( 2022) found no evidence that plant host species clustered on their X. fastidiosa phylogeny, but the samples did cluster by geography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After building a phylogeny, they tested coevolutionary relationships between host species and X. fastidiosa MLST types but found no significant evidence of coevolution, implying a lack of host specialization. This topic was recently revisited with full genome data (26,27), but the results were inconsistent between studies. Uceda-Campos et al ( 2022) found no evidence that plant host species clustered on their X. fastidiosa phylogeny, but the samples did cluster by geography.…”
Section: Discussionmentioning
confidence: 99%
“…For example, two recent papers have used phylogenies to explore the question of host specificity. In one, Uceda-Campos et al (2022) found that X. fastidiosa isolates grouped on the phylogeny by geography, but not by plant host species, suggesting host specificity is not correlated with phylogenetic relationships and genetic divergence (26). In contrast, Kahn and Almeida (2022) used the phylogeny to infer the ancestral character states of plant hosts and found that the ancestral host plant could be inferred for most ancestral nodes (27).…”
Section: Introductionmentioning
confidence: 99%